PROSES INTEGRASI NILAI SIKAP TERHADAP KETERAMPILAN MAHASISWA SEBAGAI CALON GURU: Studi Kasus Pada Mata Kuliah Telaah Kurikulum di Program Studi Pendidikan Matematika Universitas Flores - Maria Goretty Diciloam Bantas; Stefania Baptis Seto; Lely Suryani (Program Studi Pendidikan Matematika, 2021)
This study focused on seeing the character of attitudes and skills for students of mathematics education program, the University of Flores as a prospective math teacher. The purpose of this research is to know the influence of attitudes on the skills of prospective teachers. The research conducted is descriptive quantitative research, with the second-semester student population taking curriculum study courses. The data was taken using simple random sampling techniques, instruments and research data collection techniques used are observation sheets, interviews, and questionnaires of the process of integration of attitudes and skills in mathematical learning. Test validity and reliability using Product Moment correlation, the data will be analyzed using descriptive analysis techniques. The result of the research is that there is an influence on the skills of students as prospective teachers of the second semester of the University Mathematics education study program known t count value of 6,866. because the calculated t value is obtained greater than table t 2,063 so it can be concluded that H0 is rejected and Ha is accepted, which means that there is an influence of attitude (X) on student skills (Y). Judging from the significance value (sig) of 0.000 less than < probability of 0.05 so it can be concluded that H0 is rejected and Ha accepted, which means there is an influence of attitude (X) on student skills (Y).